The differential impact of the DSM-5 post-traumatic stress symptoms on functional impairment in traumatized children and adolescents. - Bartels, Lasse; Skar, Ane-Marthe Solheim; Birkeland, Marianne Skogbrott; Ormhaug, Silje Mørup; Berliner, Lucy; Jensen, Tine K. (European Child & Adolescent Psychiatry, 2024)
Background: This study aims to provide a better understanding of the individual impact of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) post-traumatic stress symptoms (PTSS) on functional impairment in trauma-exposed children and adolescents. Identifying PTSS that have the most impact on functional impairment can broaden our understanding of post-trauma reactions and guide the selection of treatment components and techniques required to help patients to restore functioning following trauma exposure. Method: Utilizing relative importance analyses, unique shared variance of each DSM-5 PTSS with functional impairment were estimated in clinical samples of 3400 Norwegian (Mage = 14.18, SDage = 2.49, rangeage = 7–17) and 747 US (Mage = 10.76, SDage = 3.10, rangeage = 7–17) children and adolescents from naturalistic settings. Results: Negative beliefs, detachment from others, inability to experience positive emotions, and diminished interest in activities within the symptom cluster negative alterations in cognitions and mood, and the hyperarousal symptom concentration problems accounted for the largest proportions of unique variance explained in functional impairment in both samples. Further, the hyperarousal symptom irritability showed a unique high association with functional impairment in the US sample. Conclusion: As negative beliefs, emotional numbing symptoms, concentration problems and irritability may be especially related to functional impairment in traumatized children and adolescents, monitoring and targeting these symptoms throughout therapy might be of particular importance to restore functioning as early as possible and to facilitate overall recovery.